Emergency department attendances and inpatient admissions due to mpox infection, England, 2022 - Taylor, Hannah; Humphreys, Clare; Verlander, Neville Q; Bhattacharya, Alex; Vivancos, Roberto; Paranthaman, Karthik (Sexually transmitted infections, 2024)
ObjectivesIn 2022, a global outbreak of mpox was reported. In the UK, it predominantly affected gay, bisexual and men who have sex with men (GBMSM). The study objectives were to describe the impact of the mpox outbreak on healthcare service usage in England in 2022, particularly emergency department (ED) attendance, inpatient admission and a number of bed days. Additionally, we wanted to explore whether pre-exposure prophylaxis (PrEP) usage, as a marker of condomless anal intercourse, which increases the risk of sexually transmitted infections associated with compromised skin integrity, was associated with higher ED attendance or hospital attendance.MethodsData on adult males with laboratory-confirmed mpox were linked with hospital records and described. Using routinely collected data and self-reported exposure data (including PrEP usage) from surveillance questionnaires, multinomial regression was used to estimate adjusted relative risk ratios (aRRRs) with 95% CIs for ED attendance and hospital admission compared with those not admitted.ResultsAmong 3542 adult males with mpox during May to December 2022, 544 (15.4%) attended ED and 202 (5.7%) were admitted to the hospital. London had the most cases (2393, 68.7%), ED attendances (391, 71.9%) and hospital admissions (121, 59.9%). In multinomial regression, we found strong evidence that compared with people living with HIV, the aRRR for hospital admissions was higher in those not using PrEP (6.9 (95% CI 2.3 to 20.6) vs 4.9 (95% CI 1.7 to 14.1)). The aRRR for ED attendance was 0.63 (95% CI 0.36 to 1.1) for those not using PrEP versus 0.49 (95% CI 0.31 to 0.79).ConclusionsThis outbreak had a considerable impact on health services, particularly in high-incidence areas. Commissioners of sexual and healthcare services should review plans for healthcare provision for similar sexually transmitted infection or novel outbreaks among GBMSM or naïve populations in the future. Further studies are needed to confirm and identify reasons for the higher likelihood of hospital admission seen for GBMSM without HIV infection.